The effect of oxide thickness on C-V characteristics for NMOS - Osman, Siti Shahada (2009)
This paper is study on the effect of oxide thickness (t₀ᵪ) on C-V characteristics for NMOS. The project being done by using SILVACO TCAD software of using ATHENA and ATLAS simulator in order to fabricate the NMOS, extract oxide thickness and see the effect to C-V characteristics. Here, t₀ᵪ of 10.13nm at time = 11 minutes, and t₀ᵪ of 10.42nm at time 50 minutes with both HCl = 3% and temperature of 900oC being used for C-V graph .The effect to C’₀ᵪ will be decreased by 12.3% when t₀ᵪ is 10.42nm. So,the t₀ᵪ of 10.13nm produced high capacitance. There also shown that there no defects in the C-V characteristics graph and the suitable t₀ᵪ to be used for NMOS.